Modern E-technologies and Academic Staff Job Productivity in Nigerian Colleges of Education - Cletus Akpo Atah; I. M. Idike; Rosemary Young Godwin; Kolo Isaac; Donatus Ugbadu Ititim; Ogbiji Michael Okpe; Ochui Moses Orim (Mediterranean Journal of Social Sciences, 2023)
The purpose of this study was to ascertain the influence modern e-technologies on academic staff productivity in Nigerian colleges of education. To achieve the study's goal, one research question was posed, and one hypothesis was developed to direct the investigation. The study utilized a survey-based design. The study's population consists of eighty-one (81) business education academic staff members, who were all participating in the research due to the population's manageable size. For data collection, an 11-item questionnaire titled "Modern E-Technologies and Academic Staff Job Productivity Questionnaire" (METASJPQ) was used. Two (2) experts validated the instrument. Cronbach's alpha reliability coefficient was 0.88 overall. To answer the research questions, the collected data were analyzed using the mean (X), standard deviation (SD), and sample percentage. An independent t-test was used to test the null hypothesis at the 0.05 level of significance. Data analysis revealed that modern e-technologies influence the productivity of academic staff in Nigerian colleges of education. In accordance with the study's findings, it was recommended, among other things, that academic staff occasionally engage students in collaborative learning via various modern e-technology platforms. Received: 18 May 2023 / Accepted: 29 June 2023 / Published: 5 July 2023